Pandemic Covid-19 and Uncertainty - Tyna Yunita; M. Fadhli Nursal; Adi Wibowo Noor Fikri; Kardina Indriana Meutia (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study focuses on entrepreneurial intention among students. The purpose of this study was to determine the factors that influence student entrepreneurship interest as a career orientation in an uncertain environmental situation. Design/methodology/approach: The statistical analysis method used is Structural Equation Modeling (SEM) where each is measured using several indicators, how uncertainty affects Career Orientation and Entrepreneurial Intentions. This research was conducted on students of the Management Study Program, Faculty of Economics and Business, Bhayangkara University, Greater Jakarta. This research was conducted by distributing questionnaires to 300 students using a simple random sampling method. Findings: The results of this study want to obtain a model that shows that uncertainty affects career orientation and student interest in entrepreneurship. Research limitations/implications: Future research is expected to explore the factors that influence student entrepreneurial intention and all aspects that encourage student career orientation. Practical implications: By involving more significant respondents in different research units, it is hoped to be used as a reference for knowledge and the basis for educational practitioners in development and decision making. Originality/value: The uncertainty of the situation is a heavy blow to the business world and the economy in general, especially business actors who are just starting their business. Historically, individuals who undertake the creation of new ventures are considered to have started an entrepreneurial career. Paper type: Research paper